Cowpea cropping systems, traits preference and production constraints in the upper west region of Ghana: farmers' consultation and implications for breeding - Benjamin Karikari; Margaret Delle Maale; Ebenezer Anning; Daniel Brain Akakpo; Afishata Mohammed Abujaja; Isaac Kwahene Addai (CABI Agriculture and Bioscience)
Abstract Background Cowpea (Vigna unguiculata (L.) Walp) is used primarily as food for humans and feed for animals. It is also used for soil management within a cropping system. However, cowpea production is confronted with numerous challenges. As such farmers and consumers alike have certain preferences in terms of production and utilization. This present study investigated cowpea cropping systems, traits preference and production constraints among farmers in the Nandom, Lambusie and Lawra districts in the northern part of the Upper West Region of Ghana. A total of 306 farming households were sampled from the 3 chosen districts. Questionnaires and interviews were used for data collection. The IBM SPSS software, version 22, was employed to analyze the data using descriptive statistics, specifically frequencies, percentages and crosstabulations. Results The study’s results indicated that a majority (58.5%) of the cowpea farmers practice intercropping, whereas a minority (41.5%) practice sole cropping. The farmers intercropped cowpea with maize, millet, sorghum and yam. Farmers preferred cowpea varieties with the following traits: high yield, drought tolerance, early maturing, pest resistance, improve soil fertility, high price, high demand, better taste, less cooking time, storage quality, palatability and fast growing. Farmers indicated that susceptibility to storage pests, high pest incidence, late maturity, difficulty in harvesting, high input cost, small grain size, low yield, high disease incidence, poor colour, lack of improved variety, and drought are some constraints that hinder cowpea production. Conclusion Results indicate a need for behavioural change communication to assist cowpea farmers to adopt improved and appropriate cropping systems. Farmers should be involved in cowpea technology development in order to understand their preferences and constraints to enable subsequent adoption of such technologies. The results from this study call for an interdisciplinary committee to plan and breed cowpea varieties that meet the needs of the farmers.